CAUSES OF DIFFERENCES IN AGING PERIOD BETWEEN PROVINCES IN INDONESIA: ANALYSIS USING PANEL DATA AND LOGISTIC REGRESSIONS - Heryanah Heryanah; Kadir Kadir (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2023)
Indonesia entered a period of aging population in 2022 with the percentage of the elderly population reaching 7% and an elderly dependency ratio reaching 10%. This aging condition is experienced differently between provinces. Some provinces have entered this period, while others haven't. This study aims to describe the process of population aging at the provincial level as well as examine the causes of differences in population aging periods between provinces in Indonesia. This study uses secondary data from the Central Bureau of Statistics covering 33 provinces in Indonesia in 2010, 2015, and 2020. Aggregate (macro) data were analyzed descriptively using the aging degree index to describe differences in the speed of the population aging process and by statistical inference using binary logistic method and panel data regression to identify causes of variations in population aging period between provinces. Logistic regression results show that provinces with characteristics of many residents migrating out, high population density, many people who already have proper sanitation, high per capita spending, and low unemployment rates, have the opportunity to enter a period of population aging more quickly than provinces without these criteria. Panel data regression results show that the aging population in Indonesia is more dominated by socioeconomic factors than demographic, health, and environmental factors. The results confirm that a holistic development approach must be pursued by the government. More attention should be given to demographic, health, and environmental aspects. Thus, population aging occurs in a quality manner accompanied by the welfare of the elderly population.